Pathogen Stimulation History Impacts Donor‐Specific CD8+ T Cell Susceptibility to Costimulation/Integrin Blockade–Based Therapy. Issue 12 (30th July 2015) - Badell, I. R.; Kitchens, W. H.; Wagener, M. E.; Lukacher, A. E.; Larsen, C. P.; Ford, M. L.
Abstract : Recent studies have shown that the quantity of donor‐reactive memory T cells is an important factor in determining the relative heterologous immunity barrier posed during transplantation. Here, we hypothesized that the quality of T cell memory also potently influences the response to costimulation blockade‐based immunosuppression. Using a murine skin graft model of CD8 + memory T cell–mediated costimulation blockade resistance, we elicited donor‐reactive memory T cells using three distinct types of pathogen infections. Strikingly, we observed differential efficacy of a costimulation and integrin blockade regimen based on the type of pathogen used to elicit the donor‐reactive memory T cell response. Intriguingly, the most immunosuppression‐sensitive memory T cell populations were composed primarily of central memory cells that possessed greater recall potential, exhibited a less differentiated phenotype, and contained more multi‐cytokine producers. These data, therefore, demonstrate that the memory T cell barrier is dependent on the specific type of pathogen infection via which the donor‐reactive memory T cells are elicited, and suggest that the immune stimulation history of a given transplant patient may profoundly influence the relative barrier posed by heterologous immunity during transplantation. Abstract : Donor‐specific T cell memory elicited by three distinct infections influences murine skin allograft survival in response to costimulation blockade‐based immunosuppression in a pathogen‐dependent manner.